Mortality from acute myocardial infarction in Brazil between 2019 and 2023: An epidemiological analysis (Research, Society and Development, 2025)
Introduction: Acute myocardial infarction (AMI) remains one of the leading causes of death in the country, with a total of 473,861 deaths recorded during the period. In analyzing AMI mortality in Brazil between 2019 and 2023, factors such as period, gender, age group, and region were considered. Objective: The present study aimed to analyze mortality from acute myocardial infarction in Brazil between 2019 and 2023 through an epidemiological analysis. Methodology: This is a quantitative, population-based descriptive study using secondary data collected from the Informatics Department of the Brazilian Unified Health System (DATASUS). Results: A reduction in deaths was observed in 2020, possibly due to underreporting during the pandemic, followed by a significant increase in subsequent years. The data indicate a higher incidence of deaths among men and the elderly over 60 years of age, with a regional prevalence in the Southeast. The COVID-19 pandemic also had a significant impact on AMI mortality patterns. Conclusion: Based on these findings, it can be concluded that there is a need for preventive strategies and public policies aimed at risk groups in order to reduce AMI mortality in Brazil.